Study on symbolism of Malay Islamic cultural heritage in Malaysian visual arts: found in Syed Ahmad Jamal artworks / Nurkhazilah Idris...[et.al] - Idris, Nurkhazilah; Mohammad Noh, Liza Marziana; Dasuki, Shaliza; Mohd Yussof, Fatrisha; Mohd Radzi, Fazlina; Muhamad Khalil, Musaddiq (2016)
This critical analysis is about the study on symbolism of Malay Islamic cultural heritage in Malaysian visual arts found in Syed Ahmad Jamal artworks particularly on the Sirih Pinang (1982), Tulisan (1961) and Mandi Laut (1957). The reason why this particular painting was chosen as the medium for a critical analysis was because of Syed Ahmad Jamal’s profound involvement in pioneering the Abstract painting movement in Malaysia with brilliant employment of symbolism of cultural elements in his works. He can be considered as one of the earliest Malaysian painter between the era of 1960s and 1970s to masterfully use the symbolism elements in translating metaphors and professing intrinsic meanings in his artwork (Syed Ahmad Jamal Sempena Malam Anugerah Seni Negara, 1995). This research is looking at the meaning behind the symbol of cultural heritage employed by the artist on his art work. It is hoped that this research would reach out to the public and further provide a bridge linking the public’s understanding with matters related to the visual arts, enlightening the meanings behind an artist’s effort and encourage public appreciation and understanding on the context of cultural heritage in visual arts. The research would also try to reflect and convey to the public on the nature of an artwork created from the symbol of Malay Islamic cultural heritage elements, when being further analysed would profess intrinsic and insightful meaning.